2003
DOI: 10.1097/01.lab.0000085190.99749.15
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Cytoplasmic TFF2 Is a Marker of Tumor Metastasis and Negative Prognostic Factor in Gastric Cancer

Abstract: SUMMARY:Trefoil factor family 2 (TFF2) is a small peptide constitutively expressed in the gastric mucosa, where it plays a protective role in restitution of gastric mucosa. TFF2 has also been shown to be expressed in some gastric cancers, but its role in tumor metastasis and patient prognosis has not been examined. In this study, we examined TFF2 expression at both the mRNA and protein levels and correlated these results with the clinicopathologic characteristics and prognosis of gastric cancer patients. Among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
34
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 26 publications
(48 reference statements)
3
34
0
Order By: Relevance
“…Digoxigenin-labeled sense and antisense RNA probes were transcribed by T7 and SP6 RNA polymerase, respectively, with a DIG RNA labeling kit according to the manufacturer’s instructions (Boehringer Mannheim, Mannheim, Germany). Hybridization and immunohistochemical steps were done, as we have described previously [9]. …”
Section: Methodsmentioning
confidence: 99%
“…Digoxigenin-labeled sense and antisense RNA probes were transcribed by T7 and SP6 RNA polymerase, respectively, with a DIG RNA labeling kit according to the manufacturer’s instructions (Boehringer Mannheim, Mannheim, Germany). Hybridization and immunohistochemical steps were done, as we have described previously [9]. …”
Section: Methodsmentioning
confidence: 99%
“…Fundic atrophy from chronic H. felis infection in mice has been associated with mucous metaplasia characterized by increased expression of trefoil factor 2 (TFF2), also known as spasmolytic polypeptide, by gastric mucous neck cells (15,43). This lesion appears to be a replacement of parietal and chief cells with TFF2-secreting mucous cells that are similar in morphology to antral or Brunner's glands and has been suggested to be a precursor lesion of gastric cancer in mice (19) and in humans (9,40). Alternatively, because TFF2 Ϫ/Ϫ mice infected with H. pylori (17) or H. felis (25) developed more severe gastritis and hyperresponsiveness to IL-1␤ than wt mice, TFF2 may be a negative regulator of gastritis, and the promotion of mucous metaplasia by wt T R cells may reflect a protective TFF2-associated response through an unknown mechanism.…”
Section: Using T-cell Transfer Into H Pylori-infected Rag2mentioning
confidence: 99%
“…To date, a number of mecha-nisms have been proposed to account for the invasive nature of TFF-expressing tumors, including the activation of several growth-promoting genes and the inhibition of apoptosis-related pathways. In an earlier study, we speculated that the invasive phenotype of TFF2-expressing tumors might be related to the induction of the neovascularization (18). Interestingly, Rodrigues et al (19) recently provided concrete evidence for the induction of angiogenesis by the TFFs in an in vitro study.…”
mentioning
confidence: 99%
“…Although the mechanisms are not understood, expression of TFFs is often dysregulated in cells during the progression to invasive cancer (15 -17). Recently, we showed that the overexpression of TFF2 is common in gastric carcinoma and is often associated with cancer invasion, metastasis, and a poor prognosis (18). Similarly, Yamachika et al (17) reported that patients with TFF3/ITF-positive gastric carcinomas also show invasive characteristics and a poor prognosis.…”
mentioning
confidence: 99%